Levantamento dos requisitos de uma ferramenta computacional de apoio à sala de aula invertida - Almeida, Lucianna Marylin Batista de (2018)
The constant transformations provided by information and communication technologies (ICT) enabled the improvement and emergence of teaching-learning methodologies innovating and transforming the educational reality. Among these modalities, the flipped classroom stands out in this research, an active learning proposal that changes the organization logic of classroom teaching, in which content is studied before students attend class, emphasizing the student in the pursuit of knowledge and teamwork during the resolution of tasks, giving opportunities to experience educational practices that allows the simultaneous execution between theory and practice. However, when using this methodology a problem that occurs during its application is the difficulty for the teacher (facilitator) to follow the whole process of development of the activities carried out outside the classroom. Thus, this research had as objective to perform a situational diagnosis of the practices and difficulties found by the educators in the application of the flipped classroom, serving as a basis to delimit the requirements for a multiagent system to support the flipped classroom according to the needs with the objective of correcting the problem inherent to the implementation of this learning theory. The methodological referrals are based on three types in the methods desing: thinking, user-centered and interactive, in which due to resemble in several points, it was chosen to briefly describe a summary of activities developed at each stage, with the aspects related to each of them emphasizing that the set of these stages compose the cycle of development of this research. The methodological foundations of the research are supported by Apolinário's criteria (2016) and by the formulation of two hypotheses proposed by Morettin (2010). Thus, the result of this research was the creation of a specific module to support educators during the application of the flipped classroom, inserted in moodle